Deep excavation practices in Singapore - U Kar Winn (2008)
In land-scarce Singapore, almost all the high-rise building construction and largescale major civil engineering works like Expressway and Mass Rapid Transit System (MRT) require deep excavation. Various types of vertical wall systems such as soldier pile walls, contiguous bored pile walls, secant pile walls and diaphragm walls are commonly used in deep excavation for basement car park and cut and cover tunnel construction for Expressways and MRT underground stations. Reinforced soil method and soil nailing are used to stabilize the vertical cut slopes in some places.